Social Protection and Labor at the World Bank, 2000-08 - Holzmann, Robert (Washington, DC : World Bank, 2012)
In autumn 2000, the World Bank's board approved the first ever strategy for the new social protection and labor sector, and in January 2001, the sector published the strategy. The subtitle, from safety net to springboard, indicated the World Bank's move toward a broader understanding of poverty reduction and the relationship of risk to poverty. Because risks and access to appropriate risk management instruments matter for poverty reduction and development, the strategy proposed a new conceptual framework - social risk management that will review and reform existing interventions and propose new ones to better assist the vulnerable in addressing the many risks to which they are exposed. After seven years of implementation, it was time to review the strategy and work of the areas of selected core competence: labor market, social insurance (in particular pensions), social safety nets, social funds, disability and development, and risk and vulnerability analysis. The strategic position, its development, and the results by the sector since the launch of its strategy were reviewed and presented to the World Bank's committee on development effectiveness at the end of 2007. The review included a stocktaking of the analytical work and lending operations in each of the six core competence areas. The result of this review and the six stocktaking papers are presented in this publication. They reveal the progress that the World Bank has made in understanding the importance of social risk management for poverty reduction and the critical contribution it makes to equitable and sustainable growth.